Penanda Hubungan Referensi (Pengacuan) Pada Wacana Cerita Pendek Surat Kabar Kompas Edisi Februari 2017 Dan Relevansinya Sebagai Bahan Ajar Bahasa Indonesia SMA - Prameswari, Rosi Lintang; , Dra. Atiqa Sabardila, M. Hum (2017)
Rosi Lintang Prameswari/A310130111. Markers Related References (Reference) in Wacana Short Story of Newspaper Kompas Edition February 2017 and Relevance as Materials Teaching Indonesian High School. Essay. The Faculty of Teacher Training and Education. University Muhammadiyah Surakarta. Juni, 2017. This study aims to: (1) describe the form of reference (reference) in the discourse of the short storynewspaper Kompas February 2017. (2) describing the relationship markers form reference (reference) in the discourse of the short storynewspaper Kompas February 2017. (3) describes the use of a marker of relationship reference (reference) in the discourse of the short story newspaper Kompas February 2017 as a high school teaching materials Indonesian. The data collection technique used is the technique of the literature, see, and record. The data analysis technique used is a unified method and agih. The validity of the data used is triangualasi engineering theory. The results of this study ere (1) Form of reference consists of the personal pronoun reference, demonstrative, and comparative. (2) Being personal pronoun references which includes persona I form aku, ku-, -ku, saya, kita and kami. Person II form, -mu, kamu, kau, dan kalian. Person III form -mu, kamu, kau, and kalian. Reference demonstrative past, neutral, present, and future. Reference demonstrative rather distant place with the speaker, much to the speaker, refers explicitly, and close to the speaker. Comparative references forms such and similar. (3) The results of this study are used as teaching material in class XI High School with 4 KI and KD 4.2, the students were asked to produce a short story text.